Professional Training of Primary School Teacher to Organize Dialogic Learning for Students: Theoretical Context - Fomin, Kateryna (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The urgency of the problem of future primary school teacher training for dialogic learning of students taking into account modern challenges of globalization and digitalization of education is substantiated. The contradictions taking place in the practice of professional training in pedagogical universities are emphasized. The theoretical aspect of the outlined problem is highlighted. The characteristics of the content of the following concepts are given: dialogic learning, educational dialogue, dialogic communication, pedagogical communication, the teacher’s communication culture, communication etiquette, etc. The components of teachers’ pedagogical skills as personal and professional factors of successful organization of dialogic learning in school are presented. It is proved that the organization of dialogic learning at school requires the formation of a teacher's system of skills, namely: to organize and manage the dialogic process in learning; create a positive communicative atmosphere for the exchange of thoughts and ideas; pedagogically expedient to stimulate communication between students; apply advanced dialogic learning technologies; motivate students to create or solve educational tasks using productive dialogue; effectively use means of verbal and nonverbal communication; make emotional contact and listen to the interlocutor, etc. The strategy of communicative approach in the educational process of the pedagogical university is widespread, first of all as for humanities. The author notes that the readiness of future primary school teachers to organize a productive educational dialogue is determined not only by the level of development of communicative abilities and skills, but also other personal traits: intellectual qualities, motivation for teaching, love for children, emotional balance, empathy, tolerance, professional responsibility, high level of moral culture, readiness for innovative activity, desire for self-improvement and self-education, etc. The author's material from the dissertation “Training of primary school teachers to organize dialogic learning” for the degree of Doctor of Philosophy (2020) is partially used in the article.